Effects of meteorological factors on mosquito density in China: results from an ongoing surveillance study in Zhejiang Province - Wang, Jinna; Song, Zhilong; Gong, Zhenyu; Luo, Mingyu; Liu, Qinmei; Li, Tianqi; Guan, Zhou; Sun, Jimin; Jiang, Jianmin (Frontiers in Climate, 2026)
ObjectivesThis study aimed to investigate the effects of meteorological factors on mosquito density by using a generalized additive model (GAM), and provide a scientific basis for the surveillance and early warnings of mosquito-borne diseases in Zhejiang Province.MethodsData on adult mosquito and larvae density were collected through ecological surveys conducted across Zhejiang Province, China, from 2017 to 2023. Meteorological data were obtained from the National Tibetan Plateau Data Center. The Kruskal-Wallis H-test and Chi-square test were used for the descriptive analysis of mosquito distribution characteristics, and Spearman rank correlation was used for the correlation of density indices. GAMs were developed to analyze the influence of meteorological factors on mosquito density. A value of p < 0.05 was considered statistically significant.ResultsThe average adult mosquito density was 10.16 per light night from 2017 to 2023 in Zhejiang Province, which exhibited a unimodal curve, peaking at 21.76 per light night in July. The average Breteau Index (BI) was 12.45. GAMs revealed that adult mosquito density and BI with or without a time lag were positively correlated with average air pressure, average monthly relative humidity, monthly sunshine hours, and average monthly temperature (all p < 0.05). Adult mosquito density and BI increased sharply below 17 °C, plateaued from 17 °C to 23 °C, and declined above 23 °C. Adult mosquito density and BI were both increased with rising humidity, and increased with monthly sunshine up to 220 h, then declined slightly above 220 h. Adult mosquito density increased with the growth of air pressure, while BI was highest when the air pressure was 970 hPa. The monthly precipitation had no contemporaneous effect on adult mosquito density or BI, yet it exerted a lagged effect on BI.ConclusionCertain meteorological factors significantly influenced both adult mosquito density and the larvae density, with or without a time lag. It is crucial to incorporate the impact of meteorological factors into the ongoing processes of mosquito control, monitoring, and early warning systems.